Gate tunable photoresponse of a two-dimensional p-n junction for high performance broadband photodetector. (March 2022) - Tran, Thi Uyen; Nguyen, Duc Anh; Duong, Ngoc Thanh; Park, Dae Young; Nguyen, Duc Hieu; Nguyen, Phuong Huyen; Park, Chulho; Lee, Juchan; Ahn, Byung Wook; Im, Hyunsik; Lim, Seong Chu; Jeong, Mun Seok
Highlights: High-performance broadband photodetector based on ReS2 /Te van der Waals heterojunction. Controllable photocurrent generation mechanism of the heterojunction via back-gate tuning. Enhanced photocurrent generation through the trapping of minority photocarrier for high responsivity and large photoconductive gain. Abstract: Optoelectronic devices based on two-dimensional (2D) van der Waals (vdWs) materials and their heterostructures are promising owing to their intriguing properties. However, the achievement of high-performance photodetectors over a wide detection range is still limited. In particular, detection in the near-infrared (NIR) region has not been attained successfully because of the relatively low responsivity to date. Herein, we report an efficient photodetection from visible to NIR ranges using a ReS2 /Te vdWs heterostructure. The dependence of the photocurrent on the incident power reveals that the dominant operating mechanism can be switched between the photogating effect and photoconductive effect by applying the back-gate voltage. The ReS2 /Te photodetector exhibits remarkable responsivities of 3 × 10 6  A W ‒1 at 458 nm and 1 × 10 6  A W ‒1 at 1062 nm laser irradiations, and an ultrahigh photoconductive gain (up to ∼10 8 ) resulting from the strong photogating effect. These outstanding performances demonstrate that the ReS2 /Te vdWs heterostructure is suitable for high-performance broadband photodetectors in practical applications. Graphical abstract: Image, graphical abstract